Empowering Students as Health Ambassadors in SMA Negeri 1 Kuta Utara - Cahyawati, Putu Nita (WMJ (Warmadewa Medical Journal), 2019)
SMA Negeri 1 Kuta Utara is one of the senior high schools located in North Kuta District, Badung Regency. This school does not only focus on the academic field but also non-academic sector. It is approved by the diverse extracurricular activities at this school. Some of them are student council (OSIS), Paskibraka, scouts, Red Cross youth volunteer (PMR), school security, the student association of environmental and adventure activities, and sports clubs (volleyball, basketball, karate, table tennis, tennis). On the other hand, the tight schedule of the extracurricular activities causes many students to have dense activities after school which often leads to various health issues including fainting caused by fatigue and swelter. Based on that situation, this activity aims to empower students together with the teachers who are involved in the PMR as health ambassadors for handling minor health problems in the form of early injury management and minor injuries which commonly occur in schools. This program included a talk from an expert, interactive discussions, pretest and posttest, simulations, training and mentoring which in its implementation; we were assisted by medical assistance team (TBM) from Faculty of Medicine and Health Sciences, Warmadewa University. Participants have played an active role in each activity with a percentage of attendance and active participation of 100% as the results of this program. The training and mentoring activities have been able to increase students' knowledge as it was shown in the increasing average value of post-test and pre-test by 77%. Through this activity, participants were expected to be able to train and transfer the skills acquired to other team members so that a sustainable process occurs.